2019
DOI: 10.35974/isc.v7i1.920
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Professional Development on Job Performance of Registered Nurses in Ghana

Abstract: INTRODUCTION: Continuous Professional Development (CPD) offers nurses the opportunity to improve their knowledge, skills, and also improve their performance in the healthcare setting. The purpose of the study was to examine if there is a relationship between CPD and job performance and to find if there is a significant difference of job performance when sex, age, and clinical experience are considered.  METHOD: Correlational research design was utilized; 164 registered nurses were conveniently sampled fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Indeed, over-commitment was found to be an intellectual and a motivational arrangement, which is characterised by being excessively involved in the job. In addition, professional development assists professional nurses to perform other roles within the work environments (Badu-Nyarko 2015). Thus, the professional nurses in this study perceived the work environment as welcoming, supportive and providing opportunities to participate in CPD activities.…”
Section: Over-commitment Motivesmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, over-commitment was found to be an intellectual and a motivational arrangement, which is characterised by being excessively involved in the job. In addition, professional development assists professional nurses to perform other roles within the work environments (Badu-Nyarko 2015). Thus, the professional nurses in this study perceived the work environment as welcoming, supportive and providing opportunities to participate in CPD activities.…”
Section: Over-commitment Motivesmentioning
confidence: 86%
“…There is a growing notion that nurses participate in different continuous professional development activities when they are motivated (Badu-Nyarko 2015). Pool et al (2016) suggested that professional development is largely influenced by employees' values, norms, attitudes and competencies.…”
Section: Introductionmentioning
confidence: 99%
“…9 Though there are some beginnings of good practice in continuous nursing education (CNE) and skill training in a few private hospitals. CPD participation is reported for a variety of reasons, including job satisfaction, staff morale, patient safety [19][20][21] , performance appraisal, and career and skill improvement. 22 These findings showed that both personal and professional growth have a significant impact.…”
Section: Discussionmentioning
confidence: 99%
“…In a descriptive study explored the factors that affect the performances of nurses. The study revealed that there is a lack of recognition of well-performing employees, the lack of a formal performance assessment system and poor working conditions and not participating in professional development programs (Osei et al, 2019(. The importance of continuing education for nurses is emphasized internationally through the relevant literature. The British Association of Nurses (BAN) states that all nurses are responsible for the way they practice their profession, and therefore they should be constantly taking the steps necessary to maintain and improve their professional knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%